Cerebral Hemodynamic and Ventilatory Responses to Hypoxia, Hypercapnia, and Hypocapnia during 5 Days at 4, 350 m. Issue 1 (January 2014) - Rupp, Thomas; Esteve, François; Bouzat, Pierre; Lundby, Carsten; Perrey, Stéphane; Levy, Patrick; Robach, Paul; Verges, Samuel
This study investigated the changes in cerebral near-infrared spectroscopy (NIRS) signals, cerebrovascular and ventilatory responses to hypoxia and CO2 during altitude exposure. At sea level (SL), after 24 hours and 5 days at 4, 350 m, 11 healthy subjects were exposed to normoxia, isocapnic hypoxia, hypercapnia, and hypocapnia. The following parameters were measured: prefrontal tissue oxygenation index (TOI), oxy- (HbO2 ), deoxy- and total hemoglobin (HbTot) concentrations with NIRS, blood velocity in the middle cerebral artery (MCAv) with transcranial Doppler and ventilation. Smaller prefrontal deoxygenation and larger ΔHbTot in response to hypoxia were observed at altitude compared with SL (day 5: ΔHbO2 −0.6±1.1 versus −1.8±1.3  μ mol/cmper mm Hg and ΔHbTot 1.4±1.3 versus 0.7±1.1  μ mol/cm per mm Hg). The hypoxic MCAv and ventilatory responses were enhanced at altitude. Prefrontal oxygenation increased less in response to hypercapnia at altitude compared with SL (day 5: ΔTOI 0.3±0.2 versus 0.5±0.3% mm Hg). The hypercapnic MCAv and ventilatory responses were decreased and increased, respectively, at altitude. Hemodynamic responses to hypocapnia did not change at altitude. Short-term altitude exposure improves cerebral oxygenation in response to hypoxia but decreases it during hypercapnia. Although these changes may be relevant for conditions such as exercise or sleep at altitude, they were not associated with symptoms of acute mountain sickness.